2017
DOI: 10.1039/c7cc07490e
|View full text |Cite
|
Sign up to set email alerts
|

A proton-hopping charge storage mechanism of ionic one-dimensional coordination polymers for high-performance supercapacitors

Abstract: A proton-conducting coordination polymer of anionic one-dimensional (1D) chains of Zn phosphate and protonated imidazole with the formula of [Zn(HPO)(HPO)](ImH) has been used as a novel supercapacitor material in aqueous electrolytes. This material stores charges via a proton-hopping mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…94,105,266 Meanwhile, multi-dimensional MOPs, which could be regulated through controlling the crystal growth direction, are another focus when designing the whole structures. 267 Comparing with 1D particles 87,268 and 3D porous frameworks, 2D layers structure have become increasingly attractive in recent works. 14,69,[90][91][92][123][124] 2D layer-by-layer deposited nanosheets, usually featuring with ultra-thin thickness and ultra-high specific areas, are able to offer numerous accessible reactive sites and have the potential to manufacture electrically conductive networks.…”
Section: Other Approachesmentioning
confidence: 99%
“…94,105,266 Meanwhile, multi-dimensional MOPs, which could be regulated through controlling the crystal growth direction, are another focus when designing the whole structures. 267 Comparing with 1D particles 87,268 and 3D porous frameworks, 2D layers structure have become increasingly attractive in recent works. 14,69,[90][91][92][123][124] 2D layer-by-layer deposited nanosheets, usually featuring with ultra-thin thickness and ultra-high specific areas, are able to offer numerous accessible reactive sites and have the potential to manufacture electrically conductive networks.…”
Section: Other Approachesmentioning
confidence: 99%
“…films of finite thickness). The addition of T, which is usually related to the diffusion resistance of ions in doped electrodes of batteries and supercapacitors, 32,35,36 indicates that VDAC36 induces a fast transfer (and a subsequent adsorption) of electrolytes on the surface of the film. This leads to an increased CPE 3L , as demonstrated by the EEC parameters (Figure 5c), indicating that npPLA/PEDOT/npPLA/VDAC films are potential candidates for the fabrication of bio-supercapacitors and -batteries for bioelectronics and bionics.…”
Section: Characterization Of the Immobilized Vdac36 Proteinmentioning
confidence: 99%
“…16−19 Other studies have reported capacitors that use proton-conductive polymers as electrolytes or electrodes. 20,21 However, examples for such studies, which focus on proton-based energy devices, remain limited. As the concentration gradient of protons between biomembranes, which can be generated by the simultaneous movement of protons and electrons, is the driving force for the production of energy in biological systems, 22,23 the proton-coupled electrontransfer (PCET) reaction should promise great potential in a variety of chemical and biological processes.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Similar to the Li ion, proton-based rocking-chair-type redox capacitors have aroused widespread interest in recent years, especially with regard to their environmental sustainability. For rocking-chair redox capacitors or all-organic proton batteries, the dissociable proton sites of the quinone/hydroquinone couple have been used. Other studies have reported capacitors that use proton-conductive polymers as electrolytes or electrodes. , However, examples for such studies, which focus on proton-based energy devices, remain limited. As the concentration gradient of protons between biomembranes, which can be generated by the simultaneous movement of protons and electrons, is the driving force for the production of energy in biological systems, , the proton-coupled electron-transfer (PCET) reaction should promise great potential in a variety of chemical and biological processes. The PCET reaction of biological systems has been mimicked using artificial molecular systems, for example, in the context of artificial photosynthesis using proton-responsive molecules. We have reported PCET reactions of redox-active benzimidazole-ligated ruthenium complexes in solution and on solid surfaces. The tridentate 2,6-bis­(benzimidazol-2-yl) pyridine (H 2 bimp) ligand contains two imino NH groups and thus behaves as a dibasic acid in solution.…”
Section: Introductionmentioning
confidence: 99%